Hiding the Horror of "Humanitarian" Warfare - Keeble, Richard (Javnost-The Public, 2000)
This study examines the growth of Britain's secret state and the media's central role in the manufacture of secret, new militarist warfare, taking the Iraq conflict of 1991 and the Kosovo crisis of 1999 as case studies. But it suggests there is no massive elite conspiracy behind these wars; they are the results of complex historical, economic, political and military factors. The institutional and personal links between journalists and the security services are another important factor examined.